Strategi Peningkatan Pendapatan Asli Desa (PADes) (Studi Pada Desa Sukarami Kecamatan Taba Penanjung Kabupaten Bengkulu Tengah) - Wijoyo, Andri; Imanda, Antonio; Yusuarsono, Yusuarsono; Kader, Bando Amin C. (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This Study aims to determine the Strategy for Increating Village Revenue (PADes) (Study at Sukarami Village of Taba Penanjung Sub-District of Central Bengkulu Regency). In this study, using a qualitative sedcriptive method. Data collection using observation tecniques, interviews and documentation. There were 6 informant in this study, namely: village Head, village Secretary, Head of Administrative and General Affairs. Head of Village Owned Enterprises, and Local Communities. The results of this study indicate that the Strategy to Increase Village Revenue (PADes) for Sukarami Village in Taba Penanjung Sub-Distric of Central Bengkulu Regency has been going well based on the theory of Fajar Supanto (2019: 111). Even though in term of human resources and limited fund/capital, Sukarami Village Government of Taba Penanjung Sub-District of Central Bengkulu Regency always carries aut their duties properly, coordinates with each other, and has a high commitment to Increasing Village Revenue (PADes).